2022
DOI: 10.3390/nu14122517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Childhood Nutrition Education from School and Family on Eating Habits of Japanese Adults

Abstract: Since the Basic Law of Shokuiku (nutrition education) was established in 2005, the Japanese government has been promoting nutrition education among children to encourage better eating habits. This study analyzes the 2019 survey data on people’s attitudes towards nutrition education, in order to elucidate the relationship between the results of nutrition education, attitude towards nutrition education and proper eating habits, and the experience of nutrition education. The results reveal that people who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Nutritional education is uncommon as they seldom discuss food-related issues in the family. A recent study showed that family conversations about food during their childhood enhanced the eating habits in adults [ 24 ]. There is a potential benefit to adolescent attitudes that comes with raised awareness through regular discussion on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional education is uncommon as they seldom discuss food-related issues in the family. A recent study showed that family conversations about food during their childhood enhanced the eating habits in adults [ 24 ]. There is a potential benefit to adolescent attitudes that comes with raised awareness through regular discussion on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that adults who ate meals regularly in childhood tend to eat meals regularly in their adulthood (in the USA) [ 39 ] and do not skip breakfast (in Japan) [ 33 ]. Several Japanese studies have shown that enjoyable eating and a good mealtime atmosphere at home during childhood promoted healthy eating behaviors, subjective diet-related quality of life, and food consciousness in adulthood [ 31 , 32 , 34 ]. It has been pointed out that caregivers talking about nutrition during childhood affected food choices and nutritional considerations among college students in the USA [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that caregivers talking about nutrition during childhood affected food choices and nutritional considerations among college students in the USA [ 39 ]. Research has shown that Japanese adults who receive nutrition education at junior high school are more likely to be interested in nutrition education in their adulthood [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations